The impact of motivation to share on the continuance of collaborative participation mediated by attitude toward consumption based on sharing economy platform - Ismi Darmastuti; Nur Afni Mustofa (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2022)
The ubiquitous adoption of information technology alongside the growth of digital business enables the widespread popularity of peer-to-peer-based activity on sharing economy platforms. In recent years, the attitudes toward consumption have gradually changed, increasing social embeddedness, environmental and ecological aspects. To begin, this research derives the influence of motivational f actors behind why users engage in sharing schemes on a shifted consumption attitude and the continuance of collaborative consumption. Data were collected through online questionnaires which were then analyzed by partial least squares (PLS) regression approach version 3.3.9 to test the model in a quantitative way involving 127 respondents as a valid sample of Gojek services users. In conclusion, this research reveals the evidence that shared ownership of accommodation through the Gojek platform is more than just a trend, but also a consumption alternative as more people participates in this kind of economic activity. The consumer's intrinsic and extrinsic motivation to share has a positive and significant influence on the continuance of collaborative participation. The attitude toward consumption strengthens as well as significantly and positively influences the relationship between motivation to share and collaborative participation, which then influences the overall consumer’s continuance participation.